PENINGKATAN PENGELOLAAN MANAJEMEN INFORMASI BERBASIS DIGITAL DI PONDOK PESANTREN ZHILALUL QUR’AN RAGUKLAMPITAN BATEALIT JEPARA - Azzah Nor Laila Azzah; Olyvia Revalita Candraloka; R. Hadapiningradja Kusumodestoni; Noor Azizah; Mu’allimatul Chasanah (Universitas Mataram, 2023)
The Zhilalul Qur'an Islamic Boarding School manages various educational services starting from the formal institutions of MI, SMP, MA, and non-formal TPQ, Madin, Tahfidz Program, and Kitab Kuning. Information services in these pesantren have been manual and uneven. Access to communication and information from administrators, ustadz/ustadzah to guardians of students is still manual, through information on the results of recording which often occurs as obstacles to tucked in archives, incomplete and not systematic. The purpose of this community service activity is to improve partners' skills in digital technology-based information management, so that services at Islamic boarding schools are more improved and developed. This service activity method starts from the socialization, training, mentoring, and evaluation stages. At the training stage the team used tutorial, lecture, and question and answer methods. Assistance phase through practical methods. The results of this service activity were 30 participants who were involved as administrators as well as ustadz ustadzah at the Zhilalul Qur'an Islamic Boarding School. After participating in digital information management training, 80% of participants were able to present activity information in digital form complete with pictures, captions through application media Canva. Previously, the participants also received training on the importance of managing information in digital-based Islamic boarding schools. Participants gain knowledge about the importance of digitization, types of information, and techniques for making news. Furthermore, assistance in the practice of making information and news designs is packaged using the Canva application media. 85% there was an increase in information services at digital-based Islamic boarding schools, information on students' return schedules, students' activities, and students' achievement progress was shared with students' guardians through digital information accompanied by pictures and interesting.